Atmospheric new particle formation in India: Current understanding and knowledge gaps. (1st February 2022) - Kanawade, Vijay P.; Sebastian, Mathew; Hooda, Rakesh K.; Hyvärinen, Antti-Pekka
Abstract: Atmospheric new particle formation (NPF), via gas-to-particle conversion, is the largest source of aerosol numbers to the terrestrial atmosphere. NPF produces about half of the present-day cloud condensation nuclei (CCN), thus significantly influencing cloud properties and Earth's energy budget. But, observations of NPF are scarce globally, particularly in India. The first-ever evidence of NPF in India was reported in 2005. To the best of our knowledge, there are only 22 published papers to date based on independent field campaigns and long-term field observations in India. These studies reported the key characteristics of NPF, such as frequency of occurrence of NPF, particle formation rate, growth rate, and atmospheric conditions influencing NPF. Very little is known about the chemical mechanisms responsible for NPF in India because field observations using state-of-the-art instruments (e.g., CI-APi-TOF, EESI-TOF) are not available for real-time identification and quantification of gas-phase and particle-phase compounds in the air. Therefore, this review focuses on the observed characteristics of NPF in different environments and identifies critical knowledge gaps for future NPF studies in India. We recommend a measurement network of aerosol and precursor concentrations in different environments using the recently developed state-of-the-art instruments aided with regional model simulations, incorporated with the nucleation schemes based on the laboratory experiments (CLOUD), to interpret field measurements. Highlights: We synthesized the current understanding of atmospheric new particle formation in India. Very little is known on physiochemical processes driving new particle formation in India. We identified the critical knowledge gaps on new particle formation in India.